Activation of Natural Killer Cells in Arthritis-Susceptible but Not Arthritis-Resistant Mouse Strains following Borrelia burgdorferi Infection - Brown, Charles R. (American Society for Microbiology, 1998)
Infection of susceptible mouse strains with Borrelia burgdorferi, the agent of Lyme disease, results in the development of arthritis. Components of the innate immune system may be important mediators of this pathology. To investigate the potential role of NK cells in development of experimental Lyme arthritis, we examined their activation in vivo in both resistant and susceptible mouse strains. Following inoculation of B. burgdorferi into the footpad, lymph node NK cells from susceptible C3H/HeJ (C3H) mice produced more gamma interferon than NK cells from resistant DBA/2J mice. Lymph node cells from susceptible C3H and AKR mice also had increased ability to lyse YAC-1 target cells 2 days following infection. Antibody depletion of NK cells from susceptible mice, however, did not alter the development of arthritis following B. burgdorferi challenge. In addition, NK cell depletion had little effect on spirochete burden. Thus, there is a marked activation of NK cells in susceptible mouse strains following infection. Although NK cells are not absolutely required for arthritis, events occurring prior to NK cell activation might be important in mediating pathology in experimental Lyme disease.